Organellar calcium pumps of the golgi and ER: from yeast to human - Rao, Rajini (Henry Stewart Talks, 2007)
Early and current views on Calcium signaling, Phylogenetic tree of Calcium-ATPases, Identification of a new family of Golgi/secretory pathway Calcium-ATPases (SPCA), Why have a Calcium pump in the Golgi?, Yeast as a model to understand Golgi Calcium pumps, Biochemical characterization of Calcium and Mn2+ transport, Phenotype screening in yeast to identify residues important for ion transport and selectivity in Pmr1, Structural and homology models of Calcium-ATPases, Golgi pumps in mammals, From structure to physiology, Haploinsufficiency of ATP2C1 leads to Hailey Hailey disease, Insights from yeast, Distribution and localization of SPCA1 and SPCA2
Archived at 2021/02/25